Great News about the Translation Work of Euthymius the Athonite - Khintibidze, Elguja (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2022)
This paper considers an article by the Danish Byzantinist Christian Høgel, “Euthymios the Athonite Greek-Georgian and Georgian-Greek translator and metaphrast?” The article reveals an essential novelty in Georgian studies: the discovery of the artistic style of Euthymius the Athonite as a Byzantine hagio- graphic writer; and an indication of his merits as an organizer of Byzantine church literature. The author of the paper Prof. Khintibidze puts forward new views on some problems of Barlaam-romance: Colophon of Iovanne the Athonite; the date and reason for the creation of Barlaam-romance; on the identity of John (Ioann) – a monk of the monastery of St. Saba.